Correlation of Body Mass Index with Waist Circumference, Random Blood Sugar and Dietary Pattern as Predictors of Diabetes Mellitus - Yadav, Sunil K.; Pathak, Renuka; Singh, Rekha K.; Mahato, Ram Vinod (International Journal of Applied Sciences and Biotechnology, 2018)
The objective of this study is correlation of body mass index with waist circumference, random blood sugar and dietary pattern to predict diabetes in university boys (18-25years). A study of random blood glucose, waist circumference and body mass index of 50 subject’s age (18-25years) was carried out. The nutritional dietary pattern of the subjects using the 24 hours dietary recall techniques was done Data was collected with a structured questionnaire. Subjects were measured for waist circumference and weight and height determent for BMI. Estimation of random blood glucose with the help of ACCU- CHECK indicated that all the boys had normal level. Subjects consisted of 50 university boys, the mean participant’s average weight is 68.21±9.31kg, average height is 173.76±7.43cm and average BMI 22.50±2.23kg/m2. Normal BMI (18.5-22.9kg/m2) was found in (48%), underweight (2%), overweight (34%) and obese (16%) of the subject studied. The mean waist circumference of participants is 85.16±6.38cm. The abnormal waist circumference (WC) was observed in 28% (n=14) and normal waist circumference is 72% (n=36) of the subject studied. The mean random blood sugar is 122.88±9.51mg/dl. The random of the subject blood sugar method is 100% normal. The nutrition intake of energy, protein, fat, carbohydrates is there mean of participants is average of energy 1786.41±335.17kcal, protein 62.70±17.4gm, fat 47.18±14.00gm and carbohydrates 256.37±59.38gm. There was a statistically positive correlation between waist circumference, body mass index and random blood sugar . Therefore, waist circumference, non-invasive techniques has a good correlation with BMI and therefore abdominal obesity is a predictor of diabetes. Int. J. Appl. Sci. Biotechnol. Vol 6(3): 274-278